Case Report: A Novel Heterozygous ZP3 Deletion Associated With Empty Follicle Syndrome and Abnormal Follicular Development - Chen, Yongzhe; Wang, Zesong; Wu, Yueren; He, Wenbin; Du, Juan; Cai, Sufen; Gong, Fei; Lu, Guangxiu; Lin, Ge; Dai, Can (Frontiers in Genetics, 2021)
Background: Empty follicle syndrome (EFS) is defined as the complete failure to retrieve oocytes after ovarian stimulation. Although several mutations in ZP1, ZP2, ZP3, and LHCGR have been identified as genetic causes of EFS, its pathogenesis is still not well-understood. Methods: Whole-exome sequencing (WES) was employed to identify the candidate pathogenic mutations, which were then verified by Sanger sequencing. A study in CHO-K1 cells was performed to analyze the effect of the mutation on protein expression. Additionally, immunohistochemistry (IHC) staining was used to examine follicular development and zona pellucida (ZP) assembly in the ovary of an EFS patient. Results: A novel heterozygous deletion in ZP3 (c.565_579del[p.Thr189_Gly193del]) was identified in the EFS patient. It was inherited dominantly and resulted in significant degradation of the ZP3 protein. Oocytes with degenerated cytoplasm and abnormal ZP assembly were observed in follicles up to the secondary stage, and many empty follicle-like structures were present. Conclusion: We identified a novel ZP3 mutation that expands the mutational spectrum associated with human EFS. We also showed the abnormal follicular development and ZP assembly of the EFS patient with the heterozygous ZP3 mutation, which provides new insights into the pathogenesis of EFS.